MANAJEMEN KURIKULUM “SEKOLAH PENGGERAK” PENDIDIKAN ANAK USIA DINI - Sopwandin, Iwan; Putri, Lisna Pitria; Muplihah, Muplihah; Pitriani, Salma; Parida, Yeni; Wahyuni, Yuni Sri (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2024)
This study aims to analyze curriculum management at Kober Andalusia Sodonghilir Tasikmalaya which is also one of the institutions selected as a School of Mover. The method used in this study is qualitative with a descriptive approach, with data collection techniques of observation, interviews, and documentation studies. The analysis techniques consist of data condensation, data presentation and drawing conclusions. Meanwhile, the data validity test is carried out with diligent observation, triangulation and audit for dependency criteria. The results of this study indicate that curriculum management at Kober Andalusia is: 1) Planning, which includes: a) making an annual program; b) making a semester program (Prosem); c) making a Learning Objective Flow (ATP); d) making a teaching module by determining Learning Achievements (CP) and Learning Objectives (TP); e) making Standard Operating Procedures (SOP); and f) making a child development program combined with the Pancasila profile independence curriculum; 2) Implementation, namely learning at Kober Andalusia using a group model that is aligned with the teaching module that has been prepared by the teacher; and 3) The evaluation in Kober Andalusia includes three things, namely: a) assessment of children with an authentic assessment approach; b) assessment of teacher performance carried out by the head of management; and c) assessment of the institution as a driving school offline and online by facilitators and available applications.